The Determinants of Occupational Success in Britain - Nickell, Stephen (Review of Economic Studies, 1982)
This paper is concerned with measuring the true impact of certain human capital variables on an individual's occupational position. The particular variables which are analysed are training, qualifications and spells of sickness and unemployment. The longitudinal nature of the data enables us to control for all relevant individual attributes which remain fixed over the period of the sample. This is vitally important because these attributes are strongly correlated with the variables of interest and would seriously corrupt estimates derived from a single cross-section. A method of generating consistent estimates (as N → ∞, T fixed) for a dynamic model with fixed effects is also illustrated.